Redefining evidence for teprotumumab in thyroid eye disease: an updated meta-analysis of efficacy and safety - Song, Rongjing; Zhao, Wei; Li, Shasha; Niu, Xiaofang; Guo, Jing; Zhang, Xiuying; Zhang, Xiaohong; Ji, Linong (Frontiers in Endocrinology, 2026)
BackgroundThyroid eye disease (TED) is a sight-threatening autoimmune disorder with limited effective therapies. Teprotumumab, an insulin-like growth factor-1 receptor inhibitor, has emerged as a promising treatment. However, a comprehensive synthesis of its efficacy and safety across randomized trials remains limited.MethodsA systematic review and meta-analysis of randomized controlled trials (RCTs) comparing teprotumumab with placebo in TED was conducted. Primary outcomes included proptosis response, overall response, change in proptosis, diplopia response, achievement of a Clinical Activity Score (CAS) ≤1, changes in Graves’ ophthalmopathy–specific quality-of-life questionnaire (GO-QOL) scores and safety outcomes. Pooled risk ratios (RRs) and mean differences (MDs) with 95% confidence intervals (CIs) were calculated using random-effects models.ResultsSeven RCTs involving 438 participants were included. Teprotumumab significantly improved all efficacy outcomes: proptosis response (RR, 6.87; 95% CI, 3.32 to 14.24), overall response (RR, 7.82; 95% CI, 3.36 to 18.18), reduction in proptosis (MD, -2.46 mm; 95% CI, -2.96 to -1.96), diplopia response (RR, 1.85; 95% CI, 1.28 to 2.68), CAS ≤1 (RR, 3.39; 95% CI, 2.41 to 4.78) and increase in GO-QOL overall score (MD, 10.87; 95% CI, 9.91 to 11.83). Safety analysis indicated elevated risks of hyperglycemia (RR, 2.82; 95% CI, 1.08 to 7.37), muscle spasms (RR, 3.83; 95% CI, 1.97 to 7.43), dry skin (RR, 6.54; 95% CI, 1.52 to 28.09), and hearing impairment (RR, 3.74; 95% CI, 1.26 to 11.13).ConclusionsTeprotumumab provides substantial, consistent benefits in improving proptosis, diplopia, disease activity and GO-QOL in TED. Clinicians should monitor for adverse events, particularly hyperglycemia and hearing impairment. These findings reinforce teprotumumab as a pivotal therapeutic option and support balanced risk-benefit evaluation.